Chemical and acoustical mixed-mapping of geological materials from laser-induced plasmas: a comprehensive approach to differentiate mineral phases - Bosáková, Markéta; Moros-Portolés, Javier; Purohit, Pablo; Álvarez-Llamas, César; Novotný, Karel; Laserna-Vázquez, José Javier (ACS, 2024)
The acoustic wave produced alongside laser-induced plasmas can be used in conjunction with the recorded atomic spectra of plasma emission to expand the physicochemical information acquired from a single inspection event. Among the most interesting uses of acoustic information is the differentiation of mineral phases with similar optical responses coexisting in geological targets. In addition, laser-induced plasma acoustics (LIPAc) can provide data related to the inspected material's hardness, density, and compactness. In this paper, we present a dual acoustic–optic laser-based strategy for the generation of high-resolution surface images of mineral samples. By combining simultaneous multimodal LIBS (laser-induced breakdown spectroscopy) and LIPAc spectral data from laser-induced plasmas, we explore the mineralogical composition of rocks embedded in resin matrixes to distinguish their chemical composition as well as their crystal phases based on physical changes caused by the different spatial arrangements of the constituent atoms. The multispectral polyhedron created by merging singular optical maps, one per detected elements, and the coincidental acoustic map enhance the distinction between regions present within the matrix of a host rock as compared to the differentiation yielded by each technique when used separately. The chemical information guides the composition of the mineral phases in the host rock. Then, the physical information obtained from acoustics may reinforce the identification of the detected mineral phase, draw the geological history of the inspected section, and showcase possible transformations, mainly of polymorphic nature. To test the combination proposed herein, we also inspected a septarian nodule featuring an ensemble of mineral phases with different origins. Mixed optical and acoustic responses from laser-produced plasmas of this complex sample allowed us to obtain more specific information.
Keywords: Rocas - Análisis; Minerales - Composición; Computer simulations; Elements; Minerals; Plasma; Quantum mechanics